2018
DOI: 10.1093/humrep/dey116
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microbiome in azoospermic men—first evidence of the impact of an altered microenvironment

Abstract: STUDY QUESTIONGiven the relevant role of the extracellular microenvironment in regulating tissue homeostasis, is testicular bacterial microbiome (BM) associated with germ cell aplasia in idiopathic non-obstructive azoospermia (iNOA)?SUMMARY ANSWERA steady increase of dysbiosis was observed among testis with normal spermatogenesis vs. iNOA with positive sperm retrieval and iNOA with complete germ cell aplasia.WHAT IS KNOWN ALREADYTissue-associated BM has been reported to be a biologically important extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 16 publications
(16 reference statements)
7
74
0
2
Order By: Relevance
“…Testes have established effective self-protection through its immunosuppressive microenvironment, which is free from pathogens and in ammatory damage [40]. Once the microenvironment of the testes is imbalanced, it may lead to the occurrence of in ammation and lesion [41]. The overexpression of IL-17A, IL-6, IL-1β, and IL-23 may change the immunosuppressive microenvironment of the testes, causing testicular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Testes have established effective self-protection through its immunosuppressive microenvironment, which is free from pathogens and in ammatory damage [40]. Once the microenvironment of the testes is imbalanced, it may lead to the occurrence of in ammation and lesion [41]. The overexpression of IL-17A, IL-6, IL-1β, and IL-23 may change the immunosuppressive microenvironment of the testes, causing testicular damage.…”
Section: Discussionmentioning
confidence: 99%
“…As an immune‐privileged organ due to the blood–testis barrier, testicular tissue is generally believed to be sterile. However, just recently, a microbiome study evaluating testicular tissue from azoospermic and testicular cancer patients revealed that many different bacterial classes can be detected by NGS (Alfano et al, ). Of further interest was the fact that the amount of bacterial DNA was increased in patients with NOA compared to those with normal spermatogenesis (Alfano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, just recently, a microbiome study evaluating testicular tissue from azoospermic and testicular cancer patients revealed that many different bacterial classes can be detected by NGS (Alfano et al, ). Of further interest was the fact that the amount of bacterial DNA was increased in patients with NOA compared to those with normal spermatogenesis (Alfano et al, ). Finally, no significant differences were identified in NOA patients with positive sperm retrieval ( n = 5) and those without ( n = 5; Alfano et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations